The Economic Impact of Real-Time Connectivity and User Readiness on Digital Health Adoption: An Extended TAM Perspective - TRAN, Anh Viet; KHOA, Bui Thanh (Theoretical and Practical Research in Economic Fields, 2025)
This study examines the key determinants of digital health application adoption, extending the Technology Acceptance Model (TAM) to incorporate the economic and practical implications of real-time connectivity and user technology readiness. Given the escalating investment in mobile health technologies, understanding the factors driving user adoption is crucial for maximizing return on digital health investments and achieving widespread public health benefits. Utilizing a quantitative research design, we applied structural equation modeling to analyze survey data from 421 potential users. Our findings confirm the significant positive influence of perceived usefulness, perceived ease of use, and user technology readiness on adoption intention, thereby expanding the TAM framework. Crucially, real-time connectivity significantly impacts TAM factors, highlighting the economic necessity of robust technological infrastructure and user preparedness for successful digital transformation in healthcare. This research offers practical implications for developers, healthcare providers, and policymakers, emphasizing the need to prioritize user-centric designs, reliable connectivity, and initiatives that enhance technology readiness to foster the widespread adoption of interactive digital health solutions and optimize their economic and social impact.